A Scholarly Examination of Tax Compliance: A Bibliometric Analysis (1960-2021) - Fauzan Fauzan; Marhaiza Ibrahim; Adi Susilo Jahja (Faculty of Economics and Business, Universitas Gadjah Mada, 2022)
Introduction/Main Objectives: Tax compliance plays a significant role in ensuring government has revenue for its expenditure. Thus, tax compliance should be understood thoroughly. Background Problems: Since tax compliance is important, a scholarly examination with bibliometric analysis is needed. This study aims to map past and current research on tax compliance to direct future research. Novelty: To the best of our knowledge, no article discusses tax compliance using bibliometric analysis. Research Methods: This study uses the bibliometric method to observe 715 documents on tax compliance research publications from the Scopus database from 1960-2021. Metadata was analyzed using Microsoft Excel for frequency analysis, VOSviewer for data visualization, and Harzing's Publish or Perish for citation metrics. Finding/Results: The number of publications on tax compliance has grown significantly. Most articles were published in journals and conferences, mainly in English. The most widely cited articles and most co-authors come from the United States, Australia, Europe, Malaysia, and Indonesia. This study identifies the widely discussed themes and possible themes for future research. Conclusion: Tax compliance studies are increasing in number and are being carried out with a multidisciplinary approach by authors from various countries. This paper also proposes some future avenues of tax compliance research. In future research, it is recommended to extend the use of databases and to include more fields in search queries.